2014
DOI: 10.1007/s00253-013-5460-2
|View full text |Cite
|
Sign up to set email alerts
|

Production of triacylglycerols in Escherichia coli by deletion of the diacylglycerol kinase gene and heterologous overexpression of atfA from Acinetobacter baylyi ADP1

Abstract: This study investigated the production of triacylglycerols in cells of the wild type of Escherichia coli and of a strain with a deleted diacylglycerol kinase gene (dgkA). By overexpression of atfA from Acinetobacter baylyi ADP1 and fadD from E. coli in the dgkA deletion mutant, cellular contents of up to 4.9% (w/w) triacylglycerols could be achieved in batch cultivation. Furthermore, heterologous expression of atfA relieves the negative effects of dgkA deletion on growth. Process optimization and fed-batch fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…coli strains with deleted genes [1720] and in wild-type (WT) E . coli strains overexpressing additional proteins [12,19,21,22]. However, recombinant oil production through the heterologous expression of a WS/DGAT has not been achieved in WT E .…”
Section: Introductionmentioning
confidence: 99%
“…coli strains with deleted genes [1720] and in wild-type (WT) E . coli strains overexpressing additional proteins [12,19,21,22]. However, recombinant oil production through the heterologous expression of a WS/DGAT has not been achieved in WT E .…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has been applied in the cyanobacterium Synechocystis as well, thereby confirming its broad applicability (Liu et al, 2011). In addition, heterologous expression of the wax ester synthase atfA may make it possible to produce fatty acid esters in some methanotrophic strains, as well as triacylglycerides if a diacylglycerol pool is present or generated (Janssen and Steinbuchel, 2014;Steen et al, 2010). Intriguingly, because methanol is generated from methane in methanotrophs, 513 it may be possible to produce fatty acid methyl esters (FAMEs) in situ without additional 514 modifications for alcohol synthesis (Fassel et al, 1992).…”
Section: Production Of Fatty Acid-derived Compounds From Methanotrophsmentioning
confidence: 70%
“…It is also known that atfA can catalyze the synthesis of triacylglycerides (TAGs) from a diacylglyceride and an acyl‐CoA molecule (Stoveken et al, ) and recently has been shown to lead to an overproduction of TAGs in E. coli (Janßen and Steinbüchel, ). This adds additional complications for optimizing FAEEs production and implies that yield of FAEEs can be diminished by side reactions of the acyltransferase.…”
Section: Resultsmentioning
confidence: 99%